Limbic System Development in Children and Adolescents with Attention Deficit/Hyperactivity Disorder: A Longitudinal Multimodal MRI Analysis - Connaughton, Michael Richard (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2024)
While Attention-Deficit Hyperactivity Disorder (ADHD) is characterized by age-related changes in symptoms and brain structures during childhood and adolescence, the link between brain structure and function is less clear. Given that prior longitudinal magnetic resonance imaging (MRI) research has predominantly focused on cortical structures, there exists a compelling need for longitudinal MRI research to investigate previously unexplored brain regions and networks, specifically the limbic system. The studies described in this thesis used multimodal MRI techniques (structural and diffusion MRI) to investigate the link between limbic system structural development and ADHD symptomology at three time points, at approximately 18-month intervals, from ages 9-14. Study 1 investigated the developmental differences in limbic system volumes among individuals with ADHD and controls using structural MRI scans processed with FreeSurfer software. The analyses of this study revealed that compared to controls, the ADHD group had lower volume in the amygdala, hippocampus, orbitofrontal cortex and cingulate gyrus across the three study time points. In the ADHD group, increased mammillary body volume growth was significantly associated with the persistence of symptom severity during mid-adolescence. Study 2 explored the development of limbic system white matter in children and adolescents with ADHD using higher-order diffusion MRI data processed with ExploreDTI software. Manual tractography isolated the key white matter tracts of the limbic system. The analyses found that compared to controls, individuals with ADHD displayed reduced microstructural organisation in the cingulum bundle and fornix across all three study time points. Study 3 investigated the development of topological organisation of the limbic system?s structural connectivity among individuals with ADHD and controls using ExploreDTI software. Results showed that reduced routing efficiency and network density were significantly associated with increased ADHD symptom severity, suggesting that underconnectivity of the limbic system may underpin increased symptom severity in ADHD. Overall, the results of the studies in this thesis suggest that atypical development of limbic system grey matter, white matter and subcortical nuclei may be a neurobiological feature associated with the persistence of ADHD symptoms during the transition into mid-adolescence.
APPROVED